2005
DOI: 10.1021/ct0500850
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Study of the NMR Spectroscopy of the Retinyl Chromophore in Visual Rhodopsin

Abstract: Abstract:The 1 H and 13 C nuclear magnetic resonance (NMR) spectra of the retinyl chromophore in rhodopsin are investigated by using quantum mechanics/molecular mechanics (QM/MM) hybrid methods at the density functional theory (DFT) B3LYP/6-31G*:Amber level of theory, in conjunction with the gauge independent atomic orbital (GIAO) method for the ab initio selfconsistent-field (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 103 publications
10
72
1
1
Order By: Relevance
“…49 In contrast, QM/MM studies found that the most significant upfield shift on C5 is due to Trp-265, with an upfield effect of -2.0 ppm. 2 This upfield effect, however, is almost completely canceled by the 1.8 ppm downfield shift due to . Therefore, it is concluded that the net upfield shift of σ C at C5 is not determined by the nearby residue with the largest upfield contribution but rather by the overall polarization of the π-system, predominantly modulated by the counterion Glu-113.…”
Section: Orientation Of the -Ionone Ringmentioning
confidence: 98%
See 3 more Smart Citations
“…49 In contrast, QM/MM studies found that the most significant upfield shift on C5 is due to Trp-265, with an upfield effect of -2.0 ppm. 2 This upfield effect, however, is almost completely canceled by the 1.8 ppm downfield shift due to . Therefore, it is concluded that the net upfield shift of σ C at C5 is not determined by the nearby residue with the largest upfield contribution but rather by the overall polarization of the π-system, predominantly modulated by the counterion Glu-113.…”
Section: Orientation Of the -Ionone Ringmentioning
confidence: 98%
“…32 An objective of recent DFT QM/MM studies has been to resolve such a contradictory picture by providing a detailed first principles description of the electronic density of the chromophore as influenced by the protein environment. 1,2 To analyze the extent of positive charge delocalization along the polyene chain, Figure 8 (upper panel) shows the distribution of electronic density difference after and before protonation of the retinyl chromophore in the rhodopsin binding site. It is shown that protonation of the Schiff base linkage induces electronic charge redistribution, driving electronic density from the polyene chain toward the NH+ bond (see violet isosurface).…”
Section: Charge Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The lower panel of Figure 9 compares theoretical and experimental values of changes in the chromophore 1 …”
Section: Primary Phototransduction Event In Visual Rhodopsinmentioning
confidence: 99%